2004
DOI: 10.1088/0953-4075/37/3/010
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted Mott scattering in the Coulomb approximation

Abstract: We investigate the influence of the Coulomb interaction on laser-assisted Mott scattering. This is done by using an approximation in which the initial state of the electron is described by a Coulomb function modulated by the laser in the same way as a relativistic Volkov state. Numerical calculations are carried out for medium field intensity, and compared with the corresponding results obtained within the first-order Born approximation (where Coulomb distortion effects are neglected). It is found that the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
4
17
0
Order By: Relevance
“…High-intensity lasers can also be employed in laser-assisted scattering processes [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], where the presence of the strong low-frequency laser field modulates a hard QED scattering process. This could be, for instance, Compton scattering where a hard x-ray (or γ-ray) photon is scattered off a (quasi-)free electron with a frequency change that depends on the scattering angle [33].…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity lasers can also be employed in laser-assisted scattering processes [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], where the presence of the strong low-frequency laser field modulates a hard QED scattering process. This could be, for instance, Compton scattering where a hard x-ray (or γ-ray) photon is scattered off a (quasi-)free electron with a frequency change that depends on the scattering angle [33].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that in many processes involving the interactions of electrons and ions (photoionization, for instance) the Coulomb potential can play an important role during the evolution of the system. For this reason, Li et al [128] analyzed the Coulomb effect over the free-free transitions in a linearly-polarized monochromatic plane wave of moderate intensity. The authors showed that the electron-ion interaction may increase the resulting cross-section at certain range of scattering angles (see also Ref.…”
Section: Mott Scatteringmentioning
confidence: 99%
“…The expression of the transition amplitude in the monochromatic case is obtained by replacing in the integrals a, 0 and 2 (11,12) the vector potential of the laser field by Eq. (16) with (φ) = 1.…”
Section: The Monochromatic Limitmentioning
confidence: 99%
“…They express the fact that the difference between the energies of the incident and scattered dressed electron can be an arbitrary integer multiple of the laser photon energy. Mott scattering beyond the Born approximation was studied by Li et al [12], using relativistic CoulombVolkov electronic states; they discussed the influence of the Coulomb distortion of the electron motion for moderate laser intensity.…”
Section: Introductionmentioning
confidence: 99%